INFLUENCE ANALYSIS OF WELDING THERMAL EFFECT IN NATURAL FREQUENCY OF SCRAPER CONVEY CHAIN DRIVE SYSTEM - ZHANG Kun; CHENG Hongyue; HE Wulin; PENG Jishen (Jixie qiangdu)
Considering the welding thermal effect of round link chain on chain drive system of scraper conveyer natural frequency,welding process and heat treatment of round link chain were simulated by using ANSYS software,and the residual stress distribution were obtained. The round link chain stiffness were obtained and were compared with the experimental values. Scraper conveyer system natural frequency were solved under idle condition and full load condition by using MATLAB software. Eighth order natural frequency and eigenvalue were obtained. The results show that:the welding thermal have greater effect on natural frequency and eigenvalue of system. Natural frequency and eigenvalue of system under full load condition are less than the idle condition’s.